A Dissertation in Preparation – Structure, Methodology, Approach and Content. The Peace Treaty of Szőny (1627) and Its Subsequent Territorial Negotiations (1628–1629) in Light of Péter Koháry’s Correspondence - MARTON, Gellért Ernő (Studia Universitatis Babeș-Bolyai Historia, 2022)
The goal of this paper is to provide an outline of the author’s dissertation in progress in terms of its structure, methodology, approach, and content. This article aims to present the author’s work on this topic so far, so it focuses on the Peace Treaty of Szőny with an emphasis on its subsequent territorial negotiations in light of Péter Koháry’s correspondence. The paper also contains an overview of Habsburg–Ottoman peace treaties, besides a summary of the afore-mentioned peace process. In this article, one can find a survey of the already collected sources (both published and unpublished). The data from these sources was entered into a database which allowed for the quantitative analysis of these exchanges of letters. The aim of the second part is to present a guide for the documents in Hungarian supplemented with examples. The examples are designed to demonstrate how the sources could be published in accordance with the rules of the guide. Rezumat: Scopul acestei lucrări este să ofere un tur ghidat prin teza de doctorat a autorului în termenii structurii acesteia, a metodei folosite, a abordării şi a conținutului. Articolul îşi propune să prezinte rezultatele cercetării autorului asupra tratatului de pace de la Szőny, punând accentul asupra negocierilor teritoriale subsecvente, în lumina corespondenței lui Péter Koháry. Articolul conține o trecere în revistă a relațiilor Habsburgo-Otomane şi a tratatelor de pace, pe lângă un sumar al negocierilor deja menționate. În acest articol putem găsi un sumar al documentelor deja colectate, atât edite cât şi inedite. Datele din aceste documente au fost integrate într-o bază de date care a permis o analiză cantitativă a acestui schimb de scrisori. Scopul celei de a doua părți a studiului este să ofere un ghid pentru documentele în maghiară şi să-l ilustreze prin exemple. Exemplele sunt alese pentru a demonstra cum ar putea fi publicate aceste surse, în conformitate cu regulile stabilite în acest ghid. Cuvinte-cheie: Péter Koháry; tratatul de pace de la Szőny (1627); negocierile teritoriale de la Szécsény şi Buda (1628–1629); relații diplomatice Habsburgo–Otomane; analiza cantitativă a unei colecții de scrisori; ghid pentru publicarea unor documente în limba maghiară